2021
DOI: 10.1016/j.jds.2020.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Surface roughness and chemical composition changes of resin-modified glass ionomer immersed in 0.2% sodium fluoride solution

Abstract: Background/purpose Glass ionomers undergo degradation when exposed to fluoride, which changes the physico-chemical characteristics of the materials. The purpose of this study was to evaluate the surface changes of resin-modified glass ionomer (RMGI) when immersed in a sodium fluoride (NaF) solution according to pH and time. Materials and methods 120 RMGI specimens were prepared, and 30 specimens were placed in four types of storage solutions for four weeks; pH 7 artific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…Specimens were embedded in a self-cured acrylic resin in a polyvinyl chloride (PVC) tube and immersed in artificial saliva 31 for 24 h. Then, the specimens were subjected to thermocycling (5 and 55 °C) with an immersion time and dwell time of 30 s and 10 s for 500 cycles according to PD ISO/TS 11405:2015 32 . Then, the specimens were placed in a shear-bond-strength testing jig under a mechanical testing frame.…”
Section: Methodsmentioning
confidence: 99%
“…Specimens were embedded in a self-cured acrylic resin in a polyvinyl chloride (PVC) tube and immersed in artificial saliva 31 for 24 h. Then, the specimens were subjected to thermocycling (5 and 55 °C) with an immersion time and dwell time of 30 s and 10 s for 500 cycles according to PD ISO/TS 11405:2015 32 . Then, the specimens were placed in a shear-bond-strength testing jig under a mechanical testing frame.…”
Section: Methodsmentioning
confidence: 99%
“…The surface of the restorative material may deteriorate as a result of high surface roughness. 16,17 Although most studies on material roughness in the literature have concentrated on fluoride gels, 11,19 a few have investigated the roughness values of fluoride varnish materials in restorative materials. 20 The literature study did not contain any studies examining the effects of fluoride varnish materials on roughness when applied to PMCR materials by heating them at different temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a complementary surface roughness test was performed, which demonstrated that none of the factors under study had a significant effect on this variable. However, the literature was controversial, since studies have shown that the action of extrinsic factors, such as food and beverage intake, can promote higher roughness values in conventional glass ionomer cements (Sari et al, 2018;Guler et al, 2021) and modified by resin (Savas et al, 2019;Ong & Yoo, 2021). This variation can occur because the surface roughness of the CIV depends on several factors, such as a) size and shape of the glass particles; b) adhesion between the particles and the matrix; c) resistance inherent to the constituents of cements, and d) reaction of setting of each material (Savas et al, 2019;Ozkanoglu & Akin, 2020).…”
Section: Discussionmentioning
confidence: 99%